Arginine Improves pH Homeostasis via Metabolism and Microbiome Modulation. (July 2017) - Agnello, M.; Cen, L.; Tran, N.C.; Shi, W.; McLean, J.S.; He, X.
Dental caries can be described as a dysbiosis of the oral microbial community, in which acidogenic, aciduric, and acid-adapted bacterial species promote a pathogenic environment, leading to demineralization. Alkali generation by oral microbes, specifically via arginine catabolic pathways, is an essential factor in maintaining plaque pH homeostasis. There is evidence that the use of arginine in dentifrices helps protect against caries. The aim of the current study was to investigate the mechanistic and ecological effect of arginine treatment on the oral microbiome and its regulation of pH dynamics, using an in vitro multispecies oral biofilm model that was previously shown to be highly reflective of the in vivo oral microbiome. Pooled saliva from 6 healthy subjects was used to generate overnight biofilms, reflecting early stages of biofilm maturation. First, we investigated the uptake of arginine by the cells of the biofilm as well as the metabolites generated. We next explored the effect of arginine on pH dynamics by pretreating biofilms with 75 mM arginine, followed by the addition of sucrose (15 mM) after 0, 6, 20, or 48 h. pH was measured at each time point and biofilms were collected for 16S sequencing and targeted arginine quantification, and supernatants were prepared for metabolomic analysis. Treatment with only sucrose led to a sustained pH drop from 7 to 4.5, while biofilms treated with sucrose after 6, 20, or 48 h of preincubation with arginine exhibited a recovery to higher pH. Arginine was detected within the cells of the biofilms, indicating active uptake, and arginine catabolites citrulline, ornithine, and putrescine were detected in supernatants, indicating active metabolism. Sequencing analysis revealed a shift in the microbial community structure in arginine-treated biofilms as well as increased species diversity. Overall, we show that arginine improved pH homeostasis through a remodeling of the oral microbial community.